2013
DOI: 10.1371/journal.pone.0059827
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation Potentiates Dihydroartemisinin-Induced Apoptosis of A549 Cells via a Caspase-8-Dependent Pathway

Abstract: This report is designed to explore the molecular mechanism by which dihydroartemisinin (DHA) and ionizing radiation (IR) induce apoptosis in human lung adenocarcinoma A549 cells. DHA treatment induced a concentration- and time-dependent reactive oxygen species (ROS)-mediated cell death with typical apoptotic characteristics such as breakdown of mitochondrial membrane potential (Δψm), caspases activation, DNA fragmentation and phosphatidylserine (PS) externalization. Inhibition of caspase-8 or -9 significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…5e), corroborating the dominant role of Bak in DHA-induced intrinsic apoptosis in HCC cells [27]. In contrast, the Bax-mediated intrinsic pathway has been reported to play a key role in DHAinduced apoptosis in various cell lines [13,[18][19][20][21][22][23][24]. Therefore, the pro-apoptotic action of DHA is cell typedependent.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…5e), corroborating the dominant role of Bak in DHA-induced intrinsic apoptosis in HCC cells [27]. In contrast, the Bax-mediated intrinsic pathway has been reported to play a key role in DHAinduced apoptosis in various cell lines [13,[18][19][20][21][22][23][24]. Therefore, the pro-apoptotic action of DHA is cell typedependent.…”
Section: Discussionmentioning
confidence: 54%
“…Accumulated proofs have shown the important role of the Bax-dependent intrinsic apoptosis pathway in DHA-induced apoptosis of multiple types of cancer cells [15,[18][19][20][21][22]. Our recent studies also demonstrated that the Bax-mediated intrinsic apoptosis pathway played a dominant role in DHA-induced apoptosis of lung cancer cells [20,23,24], while the Bak-mediated intrinsic apoptosis pathway controlled the pro-apoptotic actions of the combined treatment with DHA and gemcitabine in inducing apoptosis of A549 cells [13]. Moreover, Bak but not Bax has also been demonstrated to be the key regulator to trigger the intrinsic apoptosis pathway in DHA-induced apoptosis of Jurkat T-lymphoma cells [25].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…DHA has been reported that have co-treatment effect with many other anti-tumor compounds (Caia et al, 2004;Zongo et al, 2007;Chen et al, 2013). After enrolled into cytosol, DHA can react with Fe 2+ to generate a lot of reactive oxygen species which mediated caspase-9, -3 and/ or caspase-8 activation resulting in cell apoptosis (Mercer et al, 2007;Mercer et al, 2011).…”
Section: 5895 Dihydroartemisinine Enhances Dictamnine-induced Apoptomentioning
confidence: 99%
“…The metabolism and detoxification of xenobiotics performed by cytochrome P450 may be associated with SPN metabolism and ROS generation [36]. Therefore, the present study suggests that ROS production on A549 cells may be associated with cell death and inhibition of proliferation, as evidenced by Chen et al (2013) [37].…”
Section: Oxidative Stress In A549 Cellsmentioning
confidence: 73%